Epigenetic Regulation of Ferroptosis-Associated Genes and Its Implication in Cancer Therapy - Pei, Yanzi; Qian, Yujie; Wang, Hao; Tan, Li (Frontiers in Oncology, 2022)
Ferroptosis is an evolutionarily conserved form of regulated cell death triggered by iron-dependent phospholipid peroxidation. Ferroptosis contributes to the maintenance of tissue homeostasis under physiological conditions while its aberration is tightly connected with lots of pathophysiological processes such as acute tissue injury, chronic degenerative disease, and tumorigenesis. Epigenetic regulation controls chromatin structure and gene expression by writing/reading/erasing the covalent modifications on DNA, histone, and RNA, without altering the DNA sequence. Accumulating evidences suggest that epigenetic regulation is involved in the determination of cellular vulnerability to ferroptosis. Here, we summarize the recent advances on the epigenetic mechanisms that control the expression of ferroptosis-associated genes and thereby the ferroptosis process. Moreover, the potential value of epigenetic drugs in targeting or synergizing ferroptosis during cancer therapy is also discussed.